2015 IEEE PES Asia-Pacific Power and Energy Engineering Conference (APPEEC) 2015
DOI: 10.1109/appeec.2015.7381046
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based approach for investigating the impact of electric vehicles on power grids

Abstract: The large-scale introduction of plug-in electric vehicles (PEV) may pose challenges to power system operators by causing grid congestion or voltage fluctuations. This work presents a simulation-based approach for investigating the impact of transport electrification on power grids. The framework consists of an agent-based traffic simulation which is coupled with a power system simulation through the IEEE Standard High Level Architecture. As detailed power grid information is often unavailable, the framework fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The conductor failure due to vibration fatigue can be obtained using the CIGRE criterion introduced in [26], which considers the failure occurring when experimentally three or 10% of the total aluminum wires break, whichever proportion is greater. This experimental approach is expressed by (6) and is often referred to as CIGRE Safe Border Line (CSBL) to determine the conductor's lifetime cycles. Due to the complexity and high cost of conducting such experimentations, the CSBL has been established -so far-for conventional aluminum and aluminum alloys [39].…”
Section: Modelling Methods For Estimation Of Conductor Lifetimementioning
confidence: 99%
See 2 more Smart Citations
“…The conductor failure due to vibration fatigue can be obtained using the CIGRE criterion introduced in [26], which considers the failure occurring when experimentally three or 10% of the total aluminum wires break, whichever proportion is greater. This experimental approach is expressed by (6) and is often referred to as CIGRE Safe Border Line (CSBL) to determine the conductor's lifetime cycles. Due to the complexity and high cost of conducting such experimentations, the CSBL has been established -so far-for conventional aluminum and aluminum alloys [39].…”
Section: Modelling Methods For Estimation Of Conductor Lifetimementioning
confidence: 99%
“…The endured stresses (σa) by the conductor are determined when the conductor undergoes a bending motion for a number of cycles (Ni). The A and B coefficients in (6) are determined based on the conductor material properties which are recommended by CIGRE as tabulated in Table I. The two coefficients (A and B) in (6) are found by fitting the mean of the experimental fatigue test data, as described in [40].…”
Section: Modelling Methods For Estimation Of Conductor Lifetimementioning
confidence: 99%
See 1 more Smart Citation
“…The computational resources required for modern urban system simulations [18,4] are increasing; this has also resulted in more high resolution output data being generated. Moreover, availability of much cheaper storage options 1 has resulted in data being generated at unprecedented velocities, volumes and varieties [19,8].…”
Section: Introductionmentioning
confidence: 99%
“…The CS placement problem can also be addressed from the power grid perspective. A simulationbased approach for investigating the impact of transport electrification on power grids is presented in [31]. A case study of Singapore shows that grid 160 congestion and voltage drops are observed on the low voltage level while the high and medium voltage grid remain unaffected.…”
mentioning
confidence: 99%